STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KEDISIPLINAN GURU DI MI AL IKHLAS TIRTAJAYA KECAMATAN TIRTAJAYA KABUPATEN KARAWANG - Karman, Abdul; Hardian, Dafyar Eliadi; Mulyadi, Edi (Perspektif : Jurnal Ilmu Administrasi, 2025)
The essence of this research is to deeply understand the role and strategies of madrasah principals as educational leaders in fostering, guiding, and shaping a culture of teacher discipline within the madrasah environment. Teacher discipline is a key factor in improving educational quality, as it directly impacts the teaching and learning process and student character development. The purpose of this study was to determine the level of teacher discipline at MI Al-Ikhlas Tirtajaya, the strategies implemented by madrasah principals to foster this discipline, and the effectiveness of these strategies in improving teacher discipline. This research used a qualitative approach with a case study method. Data collection techniques included observation, in-depth interviews, and documentation. Informants in this study included madrasah principals, supervisors, senior teachers, madrasah operators, and committee chairs. The results showed that madrasah principals implemented various strategies, including setting an example, socializing and reinforcing rules, conducting regular supervision and monitoring, providing rewards and punishments, and using a humanistic and persuasive approach. This strategy has proven quite effective in improving teacher discipline, both in terms of attendance, work responsibility, and compliance with regulations. Researchers recommend that madrasah principals continue to improve consistency in implementing the strategy, involve all madrasah stakeholders in discipline development, and establish a measurable evaluation system. This way, teacher discipline can continue to improve and become a sustainable work culture within the madrasah. Keywords: Madrasah Principal Strategy, Teacher Discipline, Humanistic Approach, Case Study, MI Al-Ikhlas.